Desenvolvimento de metodologia de levantamento de características de conjugado de motores elétricos sem retirada de operação - Muniz, Pablo Rodrigues (2006)
As an alternative to the procedures used in the industry and described in technical standards, available oscillografic recorder is proposed to be used, with relative high sampling rate, to record electrical voltage and current of a motor, with posterior calculations and estimates of power supplied form the motor to the load, obtaining methodology of survey of torque characteristics of electric motors without withdrawal of the machine from the operational plant, without the needing for laboratories and workshops. As a result, good precision methodology is achieved, of low cost, not destructive, that does not interfere in the production obtained by the motor and it is fitter for industries that do not have available the motor technical documentation, or that need to validate the available documentation.